A SIMPLE CONCEPT OF ENERGY HARVESTING USING RADIO FREQUENCY - Sukumar, Nivashini; Balakrishnan, Saravanan (MATTER: International Journal of Science and Technology, 2016)
Energy harvesting is a process where certain sources is extracted and converted into DC output by connecting relevant circuits. This energy harvesting technique can reduce the usage of electricity for small power consuming devices. Some of the techniques of energy harvesting is solar energy, wind turbine, radio frequency and vibrations. Radio frequency energy harvesting can be done from the surrounding sources or from dedicated sources. This energy harvesting consists of several stages processing which starts with a 50ohms radio antenna, matching network and rectifier circuit and end as product of DC output. The proposed technique of energy harvesting is by connecting the radio antenna to an L-matching network and then to a single stage rectifier circuit to test the output obtained. The output is test using the digital multimeter in milliVolt (mV).